Evaluation of Convergence Angles in Posterior Crown Preparations by Dental Students at Zawia University - Esmeda, Fatma; Omar, Khalid A.; Eljabali, Abdussalam; Hwisa, Sara A. (Khalij-Libya Journal of Dental and Medical Research, 2024)
Background and objectives: Achieving optimal axial taper and occlusal convergence in crown preparations is a crucial concern among dental students. Proper preparation design is essential for the long-term success of full-coverage restorations. This study aimed to evaluate the convergence angles and axial taper achieved by dental students in their crown preparations. Methods. A total of 80 posterior tooth preparations (40 mandibular first molars and 40 mandibular second molars) created by second-year dental students on a dental simulator were analyzed. The total occlusal convergence (TOC), bucco-lingual (BL) and mesio-distal (MD) convergence angles, as well as the degree of taper on the axial walls, were measured using the B&B dental software (Guide system, B&B, Italy). Statistical analysis was performed using SPSS version 27. Results. The overall mean of the total convergence angle was 21.88°, with a BL convergence angle mean value of 23.11° (standard deviation of 13.3°) and an MD convergence angle mean value of 20.66° (standard deviation of 11.0°). The results showed a statistically significant difference between the mesial axial taper and the distal axial taper (p-value < 0.001). However, no significant differences were observed between the buccal axial taper and lingual axial taper (p-value > 0.05), or between the BL convergence angle and MD convergence angle (p-value > 0.05). Conclusion. The study revealed variations in the convergence angles of full metal crown preparations created by dental students. The recommended convergence angle was difficult for these students to achieve. الخلفية والأهداف: يعد تحقيق التقارب المحوري الأمثل والتقارب الإطباقي في تحضيرات التاج مصدر قلق بالغ الأهمية بين طلاب طب الأسنان. يعد تصميم التحضير المناسب ضروريًا لتحقيق النجاح الطويل الأمد لترميمات التغطية الكاملة. تهدف هذه الدراسة إلى تقييم زوايا التقارب والتقارب المحوري التي حققها طلاب طب الأسنان في تحضيرات تيجانهم. الطرق. تم تحليل إجمالي 80 تحضيرًا للأسنان الخلفية (40 ضرسًا أوليًا في الفك السفلي و40 ضرسًا ثانيًا في الفك السفلي) تم إنشاؤها بواسطة طلاب طب الأسنان في السنة الثانية على جهاز محاكاة الأسنان. تم قياس التقارب الإطباقي الكلي (TOC) وزوايا التقارب الشدقي اللساني (BL) والمتوسطي البعيد (MD)، بالإضافة إلى درجة التقارب على الجدران المحورية، باستخدام برنامج B&B لطب الأسنان (نظام Guide، B&B، إيطاليا). تم إجراء التحليل الإحصائي باستخدام برنامج SPSS الإصدار 27. النتائج. كان المتوسط ​​العام لزاوية التقارب الكلية 21.88 درجة، مع متوسط ​​قيمة زاوية تقارب BL 23.11 درجة (انحراف معياري 13.3 درجة) ومتوسط ​​قيمة زاوية تقارب MD 20.66 درجة (انحراف معياري 11.0 درجة). أظهرت النتائج وجود فرق كبير إحصائيًا بين التضيق المحوري الأوسطي والتضيق المحوري البعيد (القيمة الاحتمالية < 0.001). ومع ذلك، لم تُلاحظ أي فروق كبيرة بين التضيق المحوري الخدي والتضيق المحوري اللساني (القيمة الاحتمالية> 0.05)، أو بين زاوية تقارب BL وزاوية تقارب MD (القيمة الاحتمالية> 0.05). الاستنتاج. كشفت الدراسة عن اختلافات في زوايا التقارب لتحضيرات التيجان المعدنية الكاملة التي ابتكرها طلاب طب الأسنان. كان من الصعب على هؤلاء الطلاب تحقيق زاوية التقارب الموصى بها